N-amination of nitrogen-rich scaffolds: From single N–N bond formation to diverse energetic functionalization strategies - Le Pei; Chang-peng Xie; Ping Yin; Si-ping Pang (Energetic Materials Frontiers, 2021)
The bond-formation strategy associated with carbon and nitrogen atoms is one of the most vital fundamental techniques in the construction of organic molecules. In comparison to well-established methodologies of C–C and C–N bond formation in general synthetic chemistry, the development of N–N single bond formation for nitrogen-rich organic compounds is relatively rare. This paper summarizes the advances made in N-amination reagents and reaction conditions over the recent five years in terms of the N–N bond formation of high-energy frameworks, such as pyrazoles, 1,2,4-triazoles, 1,2,3-triazoles, and 1,3,4-oxadiazoles. Furthermore, this paper discusses the physiochemical properties of recent N-amino heterocyclic compounds and their energetic derivatives, thereby holding great promise as a guideline for rational structural modification of energetic materials. This work is aimed at providing an overall view of N-amination to access diversely functionalized energetic materials.